Spatial Evaluation of Ambon City Spatial Plan from Flood Vulnerability Aspect - Rakuasa, Heinrich; Philia Christi Latue (Jurnal Perencanaan Wilayah dan Kota, 2025)
Flooding is among the most common hydrometeorological disasters in Indonesia, including in Ambon City. This research aims to evaluate Ambon City’s 2011–2031 Spatial Plan with a focus on flood vulnerability. Using the Multi-Criteria Analysis (MCA) method, six parameters influencing flooding were analyzed: landform, elevation, land use, river buffer, soil type, and rainfall. The results indicate that the flood hazard classes in Ambon City are predominantly low (22,461.27 ha), followed by medium (9,872.83 ha) and high (1,833.07 ha) hazard areas. Notably, 50.08% (2,222.06 ha) of settlements are predicted to be affected by high flood hazard, 49.91% (2,214.67 ha) by medium hazard, and 0.01% (0.39 ha) by low hazard. Among spatial patterns, medium-density residential areas represent the largest portion of flood-affected zones, covering 532.78 ha in the high hazard class and 1,899.45 ha in the medium hazard class. In the low hazard class, buffer zones (5,127.05 ha) and agricultural areas (4,074.65 ha) are most affected. Based on these findings, recommendations include strengthening drainage infrastructure, enforcing strict zoning for new developments, and enhancing community participation in spatial planning, with the goal of increasing regional resilience to flood disasters and promoting environmental sustainability